Self-Organized Criticality in Economic Fluctuations: The Age of Maturity - Tebaldi, Claudio (Frontiers in Physics, 2021)
Bak, Chen, Scheinkman and Woodford (1993) and Scheinkman and Woodford (1994), hypothesize that emergence of macro-financial fluctuations reflects an underlying self-organized critical state. The wave of innovative thinking sparked by their proposal continues to produce interesting contributions in many areas of economics, ranging from macroeconomics to finance. In this review, we propose a guided tour to these achievements highlighting that analysis of self-organized critical equilibria is a promising avenue to establish a nexus between i) a statistical equilibrium characterized by the spontaneous emergence of dynamic critical fluctuations and ii) a strategic equilibrium concept modeling a large number of interacting players, like firms, traders, or consumers, where the critical state is the stable outcome arising from a tradeoff between cooperation and competition.